Pengembangan Desa Girikarto, Kabupaten Gunung Kidul sebagai Desa Wisata - Pabubung, Michael Reskiantio; Aldo Ario Sulistyawan; Cicilia Nandira Prasetiyono; Anastasia Telly Wijaya Kusuma; Dwi Sus Rini; I Wayan Agus Kusumajaya; Vennya Etika Monica Sari; Given Erly Nice Leiwakabessy; Lisyanti Sinaga; Charten Lungguk Tambunan; Wenseslaus Dwiyanto Putra (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2024)
Girikarto Village is a village located in Panggang District, Gunungkidul, Yogyakarta. Girikarto Village is located in the southern part of the Gunung Kidul region and is on the border of the Indian Ocean. Girikarto Village has a variety of village potentials that can be managed by the local community. This effort is needed to provide education to residents around the village of Girikarto so that they can develop the existing potentials and know the social conditions of the village. To assist the community in developing the potential of Girikarto Village, a problem identification process is carried out first. Because there is no direct fieldwork in this process, research will be carried out via the internet. From the results of the research, it is strengthened by a literature study using several sources such as books, journals, articles and news. Then the author determines the purpose of community service in Girikarto village. After determining the objectives, the data obtained were collected for the development of village potential. After selecting the data, the authors will carry out the stages of data analysis as a further development. The potentials that can be developed are coastal tourism, culinary innovations of instant tiwul, arts, and teak forests with good management of facilities and infrastructure.